PENGENALAN MODEL PEMBELAJARAN GAME BASED LEARNING DI SEKOLAH SATU ATAP (SATAP) DESA PULAU MARINGKIK MELALUI PROGRAM KONTRIBUSI SOSIAL PERTUKARAN MAHASISWA MERDEKA 3 (PMM 3) INBOUND UNIVERSITAS MATARAM TAHUN 2023 - Munir, Ahmad Mubarak; Ayuningsih, Adinda Noura; Hardiansyah, Kelfin; Syahra, Tasya Alvianka; Yusriah, Halimatul (Universitas Mataram, 2024)
The education sector in the Remote, Frontier, and Outermost (3T) regions faces several main issues including infrastructure, teacher quality, infrastructure support, and the number of teachers. Maringkik Island is one of the outermost islands facing the aforementioned problems. Its geographical condition, separated from the mainland of Lombok Island, brings its challenges for the mobility of teachers and supporting facilities for schools. Interventions in the learning model to improve the quality of education and student's interest in learning have become a separate necessity. The Student Exchange Program of PMM 3, through social contribution activities, introduces a game-based learning model at the Integrated School on Maringkik Island. The objectives of this activity include providing alternative game-based learning models that can be adapted to schools in coastal and island regions. The implementation of this activity is carried out through 5 stages: preparation, planning, needs analysis, program implementation, and activity evaluation. This activity can increase students' enthusiasm for the learning process.